Fumarate hydratase deficient renal cell carcinoma and fumarate hydratase deficient-like renal cell carcinoma: Morphologic comparative study of 23 genetically tested cases - Pivovarčíková, Kristýna; Martínek, Petr; Trpkov, Kiril; Alaghehbandan, Reza; Magi-Galluzzi, Cristina; Mundo, Enric Condom; Berney, Daniel; Suster, Saul; Gill, Anthony; Rychlý, Boris; Michalová, Květoslava; Pitra, Tomáš; et al. (Ceskoslovenska patologie, 2019)
Hereditary leiomyomatosis and renal cell carcinoma-associated renal cell carcinoma (HLRCC)/ fumarate hydratase deficient renal cell carcinoma (FHRCC) is an aggressive tumor defined by molecular genetic changes - alteration in fumarate hydratase (FH) gene. The morphologic spectrum of HLRCC/FHDRCC is remarkably variable. The presence of large nuclei and prominent dark red inclusion-like nucleoli and perinucleolar clearing are considered as helpful morphologic clue. We selected 23 renal neoplasms primarily based on their morphologic features suspicious for HLRCC/FHDRCC. Morphological, basic immunohistochemical, and genetic analysis was performed. The tumors were divided in two groups according to the molecular genetic findings. The first group included 13 tumors with detected FH mutation/LOH (compatible with diagnosis FHRCC), and the second group included 10 tumors without FH mutation/LOH (FH-like RCCs). In the FHRCC group, the vast majority of cases (9/13) had mixed morphology with different architectural growth patterns. All cases showed prominent macronucleoli, and perinucleolar clearing was found in 10/13 cases. Immunohistochemically, 6/7 FHRCC cases were negative for FH antibody, while one case showed strong diffuse FH reactivity. The FH-like RCC group showed more uniform architectural growth pattern. All 10 tumors had prominent macronucleoli, and perinucleolar clearing was present in 8/10 cases. Eight FH-like RCC cases showed diffuse strong positivity for FH, although 2 cases were completely negative for FH. It is evident that neither morphologic feature nor immunohistochemical analysis can be reliably used in routine practice for the diagnosis of HLRCC/FHRCC. In suspected cases, the diagnosis of HLRCC/FHRCC can be confirmed by molecular-genetic testing for FH mutation. It should be noted that the traditionally described morphologic features of HLRCC/FHRCC (prominent eosinophilic macronuclei with perinucleolar halos) can frequently be seen in other renal neoplasms.
Keywords: nádory ledvin; nádory kůže; nádory dělohy; Humans; dědičné nádorové syndromy; Skin Neoplasms; Leiomyomatosis; Female; fumarasa; leiomyomatóza; lidé; Fumarate Hydratase; fumarate hydratase; renal cell carcinoma; Uterine Neoplasms; ženské pohlaví; karcinom z renálních buněk; HLRCC; Carcinoma, Renal Cell; Kidney Neoplasms; Neoplastic Syndromes, Hereditary